Student Classroom Misbehavior: An Exploratory Study Based on Teachers' Perceptions - Rachel C. F. Sun; Daniel T. L. Shek (The Scientific World Journal)
This study aimed to examine the conceptions of junior secondary school student misbehaviors in classroom, and to identify the most common, disruptive, and unacceptable student problem behaviors from teachers' perspective. Twelve individual interviews with teachers were conducted. A list of 17 student problem behaviors was generated. Results showed that the most common and disruptive problem behavior was talking out of turn, followed by nonattentiveness, daydreaming, and idleness. The most unacceptable problem behavior was disrespecting teachers in terms of disobedience and rudeness, followed by talking out of turn and verbal aggression. The findings revealed that teachers perceived student problem behaviors as those behaviors involving rule-breaking, violating the implicit norms or expectations, being inappropriate in the classroom settings and upsetting teaching and learning, which mainly required intervention from teachers.